Study of Cucurbita extract effect on changes of AGEs, lipid and glycemic profile and CRP in type 1 diabetic rats (Bangladesh Journal of Medical Science, 2018)
Background: Clinically, diabetes is an important risk factor or a range of diseases including nephropathy,retinopathy, angiopathy and deficiency and it is increasing in prevalence according to some estimates. (Cucurbita pepo L.) from the cucurbitaceae family has a low calorie but high nutritional and medical value. The aim of this study was to observe the effect of cucurbita extract on serum factors of STZ induced diabetic rats including glucose level AGEs, lipid profile (cholesterol, HDL, LDL, and TG) and CRP.Material and methods: Diabetes type1 was induced to Male albino- wistar rats by STZ at a dosage of 50 mg kg-1. 17 rat were divided into three groups randomly including diabetic treated with extract, diabetic control and normal group. Diabetic group were force fed orally by cucurbita extract. The animals were anesthetized with ether at the end of 30 days and the blood was collected by syringe from their hearts for estimation of plasma glucose, TG, HDL, LDL, total cholesterol, CRP and AGEsResults: After measuring the serum factors and compares the result of the three groups to each other meaningful difference that shows the positive effect of cucurbita extract has been seen.Conclusion: According to the results we suggest that squash extract could have positive effect on regulating some of blood elements like glucose which are under the bad effect of diabetes type1 in rats. But more investigations are needed in this field to demonstrate the real benefits of cucurbita in curing diabetes and its related signs.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.84-87